Process optimization of polyphenol extraction from carob (Ceratonia siliqua) kibbles using microwave-assisted technique - Huma, Z.; Jayasena, Vijay; Nasar-Abbas, S.; Imran, M.; Khan, M. (Wiley Online Library, 2018)
© 2017 Wiley Periodicals, Inc. Microwave-assisted extraction (MAE) method was investigated to recover phenolic compounds from carob kibbles and validated using response surface methodology. The study parameters were microwave power (170–900 W), ethanol concentration (30–90%), and solvent-to-sample ratio (10–30 mL/g) in terms of total phenolic content (TPC) and condensed tannins. Among optimized parameters (340 W, 45%, 30 mL/g), microwave power and ethanol concentration were found more influential parameters to get higher yields of TPC and condensed tannins. Moreover, the results of TPC (70.11 mg GAE g-1 DM), condensed tannins (4.11 mg CE g-1 DM), free radical scavenging activity (94.42%), ferric ion reducing potential (22.67 mg Fe+3 100 g-1 DM), and gallic acid (1.576 mg/g DM) obtained from optimal MAE conditions were found comparable to ultrasound-assisted extraction method. The newly developed MAE method illustrates its potential to recover phenolic compounds from plant sources in a short duration. Practical applications: Based on the results presented in this work, it is proposed that carob kibble could be considered as interesting raw material to get extracts rich in antioxidant properties. This extract could be used as an alternative to synthetic antioxidants in bio-food products as natural preservative. Therefore, carob kibbles could be recommended for production of extracts rich in antioxidants, instead of being discarded from gum factory as by-product. In addition, microwave-assisted extraction method could be employed to increase time efficiency of the process.